Behavioral and Molecular Consequences of Chronic Sleep Restriction During Development in Fragile X Mice - Saré, R. Michelle; Song, Alex; Levine, Merlin; Lemons, Abigail; Loutaev, Inna; Sheeler, Carrie; Hildreth, Christine; Mfon, Angel; Smith, Carolyn Beebe (Frontiers in Neuroscience, 2022)
Sleep is critical for brain development and synaptic plasticity. In male wild-type mice, chronic sleep-restriction during development results in long-lasting impairments in behavior including hypoactivity, decreased sociability, and increased repetitive behavior. Disordered sleep is characteristic of many neurodevelopmental disorders. Moreover, the severity of behavioral symptoms is correlated with the degree of disordered sleep. We hypothesized that chronic developmental sleep-restriction in a mouse model of fragile X syndrome would exacerbate behavioral phenotypes. To test our hypothesis, we sleep-restricted Fmr1 KO mice for 3 h per day from P5-P52 and subjected mice to behavioral tests beginning on P42. Contrary to our expectations, sleep-restriction improved the hyperactivity and lack of preference for social novelty phenotypes in Fmr1 KO mice, but had no measurable effect on repetitive activity. Sleep-restriction also resulted in changes in regional distribution of myelin basic protein suggesting effects on myelination. These findings have implications for the role of disrupted sleep in the severity of symptoms in fragile X syndrome.